The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/03630242.2018.1487905
|View full text |Cite
|
Sign up to set email alerts
|

Seeking emergency contraception in the United States: A review of access and barriers

Abstract: Federal regulations governing access to levonorgestrel (LNG) emergency contraception (EC) have evolved since its introduction in the 1990s. LNG EC was initially available by prescription only, but is now available over-the-counter to consumers of all ages. Nonetheless, consumers seeking EC in their communities may face ongoing barriers to access, including low stock and inaccurate information provided by pharmacy staff. We conducted a review of LNG EC secret shopper studies to describe changes in EC access and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Not having generic brands available likely relates to the limited shelf space of smaller pharmacies. Previous studies have shown that some pharmacies do not stock EC due to the perception of low demand, pharmacy staff personal objection to EC, or store policy [17]. Our study found that 58% of pharmacies on Oahu have LNG EC available OTC without a lock, which is higher than previous studies that show 22% of pharmacies nationwide have LNG EC available without a lock [18].…”
Section: Discussioncontrasting
confidence: 80%
“…Not having generic brands available likely relates to the limited shelf space of smaller pharmacies. Previous studies have shown that some pharmacies do not stock EC due to the perception of low demand, pharmacy staff personal objection to EC, or store policy [17]. Our study found that 58% of pharmacies on Oahu have LNG EC available OTC without a lock, which is higher than previous studies that show 22% of pharmacies nationwide have LNG EC available without a lock [18].…”
Section: Discussioncontrasting
confidence: 80%
“…8 Mystery shopper studies relating to EC access from pharmacies have also been published from other countries such as Australia and the USA. [9][10][11][12][13] While the research question posed by each investigator was somewhat different to that of our mystery shopper study, all concluded that pharmacists' practices are variable and not always in line with the recommendations in guidelines.…”
Section: Discussionmentioning
confidence: 64%
“…Although overall EC use has increased since FDA approval of OTC sale [6] , pharmacy access remains a common problem throughout the US [ 4 , 13 ]. Barriers to EC pharmacy availability are varied, including suboptimal stocking due to perception of low demand, pharmacy staff personal objection, or placing OTC EC behind the counter or in a locked box due to concerns about theft [14] . Our findings are consistent with other studies showing that a high proportion of pharmacies choose to keep LNG in a locked box or cabinet, complicating the OTC nature of this medication [7] .…”
Section: Discussionmentioning
confidence: 99%